Abuso sexual infantil y administración de justicia en Colombia. Reflexiones desde la Psicología Clínica y Forense (2011)
ABSTRACT: The analysis of research carried out in Colombia to clarify legal events regarding the phenomenon of child sexual abuse facilitates the identification of problem areas in the application of justice, with reference to the legal investigation and psychological evaluations which are frequently carried out in an inadequate manner. The intention is to draw attention to the frequency of these events in the taking of judicial decisions, which could violate citizens' rights. Some of main restrictions which obstruct the work of the players in the judicial sector, especially that of the psychological forensic scientist, are explained by the inadequacy of the Colombian state in correctly applying the Law of Childhood and Adolescence, since the procedures and functions provided by the law are often disregarded. Also considered is the frequency with which the great social pressure which falls on those who have legal responsibility in these cases, and which in some cases slows down the correct legal processes. Thus, apart from describing the habitual difficulties which are present in the evaluation of the evidence given by children, allied to the emerging cognitive development and the material dependence and affective respecto for the adults, other reasons are demonstrated which complicate the processes of legal and psychological investigation in cases of child sexual abuse. Finally, some of the minimal clinical elements which should be considered in psychological investigation are described, with the aim of overcoming the aforementioned restrictions and problems, based on the coordination of clinical and forensic approaches.